2016
DOI: 10.1177/0306624x16670951
|View full text |Cite
|
Sign up to set email alerts
|

Do Extremely Violent Juveniles Respond Differently to Treatment?

Abstract: This study increases knowledge on effectiveness of treatment for extremely violent (EV) youth by investigating their response to multisystemic therapy (MST). Using data of a randomized controlled trial on effectiveness of MST, we investigated differences in treatment response between EV youth and not extremely violent (NEV) youth. Pre- to post-treatment comparison indicated MST was equally effective for EV and NEV youth, whereas treatment as usual was not effective for either group. Growth curves of within-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…Conversely, youth in the detached and weakly bonded subtype may be better served by trauma-focused therapy, as it is designed to address the issues those youth are specifically affected by. Finally, youth in the problematic peers subtype may benefit most from a comprehensive treatment such as multisystemic therapy (Connell et al, 2016), which addresses risk factors in the home and school environments to improve parental supervision, impulse control, and performance at school, all of which may promote the value of school, decrease associations with delinquent peers, and reduce risk of offending (Asscher et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, youth in the detached and weakly bonded subtype may be better served by trauma-focused therapy, as it is designed to address the issues those youth are specifically affected by. Finally, youth in the problematic peers subtype may benefit most from a comprehensive treatment such as multisystemic therapy (Connell et al, 2016), which addresses risk factors in the home and school environments to improve parental supervision, impulse control, and performance at school, all of which may promote the value of school, decrease associations with delinquent peers, and reduce risk of offending (Asscher et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The research underlined the value of tailored therapy that consider the unique characteristics and risk factors associated with serious violence. Further research is needed to adequately meet the therapeutic requirements of this specific juvenile group (Asscher et al, 2018). The effect of exposure to potentially morally injurious events on the mental health outcomes of juveniles involved in the juvenile justice system is examined and it indicates that, even after adjusting for trauma exposure and demographic variables, PMIEs are strongly linked to symptoms of depression, anxiety, and non-suicidal self-injury (NSSI).…”
Section: Mental and Psychological Factormentioning
confidence: 99%
“…For instance, a study of extremely violent delinquents among whom 10% were homicide offenders found that Multisystemic Therapy produced increased antisocial behavior among violent youth during the first month of its use, but then produced reductions in aggressive conduct. Unfortunately, those reductions produced very small effect sizes, and the evaluation period spanned a mere 4 months from the start of the intervention (Asscher et al, 2018). Earlier work had already shown that Multisystemic Therapy decreased externalizing problems only among those deemed "lower callous/unemotional" and "lower narcissism," suggesting the limited utility of treatment among adolescents with more extensive psychopathic traits (Manders et al, 2013).…”
Section: Externalizing Psychopathology and Incorrigibilitymentioning
confidence: 99%